The genomic region matters when synthesizing dsRNA for plant virus suppression via RNAi - Karol Barroso; Juliana Milagres; Talia Tracton; Teja Shidore; Raja Muthuramalingam; Rania El-Tanbouly; Márcia Ambrósio; Washington da Silva (Virology Journal)
Abstract Plant viruses are one of the most economically important plant pathogen groups in the world, and there is no viricide available for their control. Therefore, RNA interference (RNAi)-based crop protection has become a promising strategy for the control of viral plant pathogens in agricultural systems. Herein, we aimed to test the hypothesis that exogenously applied dsRNA molecules derived from different viral genomic regions induce different levels of viral suppression by RNAi in plants. We also evaluated the fate and movement of the dsRNA molecules inside tobacco plants. We synthesized dsRNAs from three potato virus Y (PVY) cistrons, helper component-protease (HC-Pro), nuclear inclusion protein b (NIb), and coat protein (CP), and applied them to tobacco leaves to test our hypothesis. Our results indicated that all three dsRNAs applied can provide some level of protection to plants against PVY infection. However, the intensity and longevity of protection depend on the type of dsRNA applied. HC-Pro-dsRNA induced greater protection, entered, and moved faster in tobacco plants than dsRNAs from NIb and CP cistrons. Furthermore, dsRNAs were detected in systemic leaves after 24 h of dsRNA application and remained for at least 14 days, demonstrating that these molecules translocated systemically inside the plant. The synthesis and application of exogenous dsRNAs targeting the HC-Pro genomic region of PVY appear to be a promising strategy for controlling PVY. Moving forward, we are working on developing a delivery system to sustainably provide plants with those molecules to create viricides for practical agricultural applications.